2007
DOI: 10.1111/j.1399-0039.2006.773_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of variants in the IL12B gene with leprosy and tuberculosis

Abstract: There is a great range in outcomes after mycobacterial infections, and this is probably due to individual variation in immune responses. One of the key cytokine regulators of the immune response is interleukin (IL-) 12. The IL12B gene encodes the p40 chain of both IL-12 and IL-23 and it has two major variant sites at which different alleles are associated with increased levels of gene expression and with susceptibility to a range of immune-related diseases. We hypothesized that IL12B variants associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
5
25
1
1
Order By: Relevance
“…Our results also indicate that two known cisregulatory element polymorphisms, IL12Bpro and IL12B 3 0 UTR, did not strongly influence parasitemia, despite the associations between IL-12 levels and P. falciparum parasitemia, 19 between IL12Bpro and cerebral malaria 6 and the association of several diseases related to immune responses with IL12Bpro and IL12B 3 0 UTR. 20,22,23,31 Since IL12B polymorphisms may interact, such that different haplotypes exhibit different IL-12 levels, 23 we also evaluated the association of parasitemia with haplotypes, including the IL12Bpro-IL12B 3 0 UTR haplotypes; we detected the association of parasitemia with neither haplotypes based on the seven polymorphisms identified nor with IL12Bpro-IL12B 3 0 UTR haplotypes. This suggests that parasitemia is not influenced by genetic variation in IL12B, including IL12Bpro and IL12B 3 0 UTR polymorphisms.…”
Section: Il12b In Human Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also indicate that two known cisregulatory element polymorphisms, IL12Bpro and IL12B 3 0 UTR, did not strongly influence parasitemia, despite the associations between IL-12 levels and P. falciparum parasitemia, 19 between IL12Bpro and cerebral malaria 6 and the association of several diseases related to immune responses with IL12Bpro and IL12B 3 0 UTR. 20,22,23,31 Since IL12B polymorphisms may interact, such that different haplotypes exhibit different IL-12 levels, 23 we also evaluated the association of parasitemia with haplotypes, including the IL12Bpro-IL12B 3 0 UTR haplotypes; we detected the association of parasitemia with neither haplotypes based on the seven polymorphisms identified nor with IL12Bpro-IL12B 3 0 UTR haplotypes. This suggests that parasitemia is not influenced by genetic variation in IL12B, including IL12Bpro and IL12B 3 0 UTR polymorphisms.…”
Section: Il12b In Human Malariamentioning
confidence: 99%
“…6 Furthermore, a stronger association was found between cerebral malaria and an haplotype based on IL12Bpro and one polymorphism in the 3 0 untranslated region (UTR) of IL12B (rs3212227). 6 Interestingly, the IL12B 3 0 UTR polymorphism has been associated with several diseases related to immune responses, 22,23 and with variation in the production of IL-12. 22 To our knowledge, this was the only report of an association between IL12B and human malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepant results have been reported among various populations regarding the link between TB and IL-12 polymorphisms (especially for IL-12B, the gene encoding the IL12p40 subunit). Several IL-12B polymorphisms in the introns, promoter, or 3=-UTR were found to be associated with TB in some studies (83,151,236) but not others (132,173,201). An IL-12B 3=-UTR SNP (rs3212227) was identified as a risk factor for pulmonary TB in populations of African origin in a confirmation study (152).…”
Section: Il-12mentioning
confidence: 99%
“…In contrast to our findings, Morris et al (20) revealed an association between IL12B rs3212227 and PTB risk in Guinea-Bissau and African-Americans population. Morahan et al (21) showed that the distribution of 3' UTR genotype of IL12B gene was different between the TB patients and control groups, besides they demonstrated a positive correlation between the expression of IL-12 and this polymorphism. They suggested that this polymorphism can cause increased IL-12 expression.…”
Section: Reverse Outer Agctcctctcactggtcccctt Forward Inner (A Allelementioning
confidence: 99%